Do institutional investors unbind firm financial constraints? Evidence from emerging markets (2016)
Using firm-level information for 11 large emerging economies for the 2003-2014 period, this article analyses the impact of firm investment ratio depending on the presence of institutional ownership and the effects of institutional investor heterogeneity on firm financial constraints. Results show that the presence of institutional ownership reduces firm cash flow sensitivity for restricted samples using size and the Kaplan and Zingales index. Investor heterogeneity regressions show that independent and foreign institutional investors reduce firm financial constraints explained by direct investor activism, lower monitoring costs and better corporate governance in particular across small and medium-size firms.